Pandanus tectorius Leaf Extract Protects Gnotobiotic Brine Shrimp Artemia franciscana Against Vibrio campbellii Through Immunomodulation and Virulence Suppression - Sarath Kumara Patabandi; Cher Chien Lau; Yosie Andriani; Patrick Sorgeloos; Kartik Baruah; Parisa Norouzitallab; Yeong Yik Sung (Journal of Fish Diseases, 2026)
The bacterial disease vibriosis in farmed shrimps typically occurs when the host immunity is compromised, creating favourable conditions for pathogenic vibrios to proliferate and express virulence factors that contribute to disease development. Therefore, effective control of vibriosis requires interventions that not only enhance host immune competence but also attenuate pathogen virulence. This study evaluated whether Pandanus tectorius leaf extract (PLE) could protect farmed shrimp against vibriosis through a potentially dual mode of action: enhancing host immune responses and simultaneously suppressing virulence traits in the pathogen. To address this, germ‐free brine shrimp Artemia and Vibrio campbellii were used as a host‐pathogen model system. Germ‐free Artemia were persistently exposed to PLE (0.2–3.0 g/L) and simultaneously challenged with V. campbellii (10 6 cells/mL). Host immunomodulatory effects were assessed through the expression of immune‐related genes, whereas anti‐virulence activity was evaluated by measuring bacterial growth, motility, and extracellular enzyme production. Exposure to PLE at 0.2–0.8 g/L significantly enhanced the survival of challenged Artemia nauplii, resulting in survival rates exceeding 90%. This protection was associated with the upregulation of key immune‐related genes, including heat shock proteins ( Hsp70 and Hsp60 ), prophenoloxidase, transglutaminase, and high mobility group box‐1. Results also showed that PLE at concentrations as low as 0.2 g/L exerted direct inhibitory effects on V. campbellii , effectively reducing bacterial growth, swimming and swarming motility, and virulence‐associated enzymatic activities, including caseinase, lipase, and phospholipase. No adverse effects on Artemia survival were observed within the tested doses and exposure period. Overall, the findings suggest that PLE holds strong potential as a natural immunomodulatory and anti‐virulence agent for sustainable management of vibriosis in shrimp aquaculture.